Improving reviewer selection in Open Journal Systems using a Scopus search application programming interface in the - Indra Kharisma Raharjana; Badrus Zaman; Oktavia Intifada Husna; Rizfi Ferdiansyah; Aretha Seno Putri; Fariska Dwi Kartika Sari (Science Editing)
Purpose The peer review process is essential for maintaining the quality of scientific publications. However, identifying reviewers who possess the necessary expertise can be challenging. In Open Journal Systems (OJS), which is commonly utilized by journals, the most effective method of inviting reviewers is when they are already registered in the system. This study seeks to improve the efficiency and accuracy of the reviewer selection process to ensure high-quality peer reviews. Methods We introduced a process innovation to analyze users within OJS and obtain recommendations for potential reviewers possessing the relevant expertise for the manuscript under review. This study collected user data from OJS as potential reviewers and utilized information from the Scopus search application programming interface (API). We extracted authors’ data from the Scopus API to obtain their Scopus IDs, which were then used to scrape publication data of potential reviewers. The system matched the previous works of reviewers with the title and abstract of the manuscript using term frequency-inverse document frequency and cosine similarity algorithms. Results The system was evaluated by comparing its recommendations with the assessments made by the editorial team. This evaluation yielded precision, mean average precision, and mean reciprocal rank values of 0.47, 0.77, and 0.87, respectively. Conclusion The results clearly demonstrate the system’s ability to provide relevant reviewer recommendations. This system offers significant benefits by assisting editors in identifying suitable reviewer candidates from the existing user database in OJS, particularly for the evaluation of manuscripts.